Education for the disabled in accordance with the quality of inclusive education in the distance education process - Stambekova, A.; Zhakipbekova, S.; Tussubekova, K.; Mazhinov, B.; Shmidt, M.; Rymhanova, A. (World Journal on Educational Technology: Current Issues, 2022)
The aim of this research is to evaluate the disabled education in accordance with the quality of inclusive education in the distance education process in line with the opinions of special education teachers. The research was conducted with 10 special education teachers who were teaching special education and general education in schools with special needs students in Kazakhstan and who agreed to participate in the research voluntarily. The research was designed in accordance with the case study, one of the qualitative research designs. Research data were collected with a semi-structured interview form developed by the researchers. As a result of the research, it was revealed that the teachers used online lessons, video sharing, homework control, online activities and mobile applications in the teaching of the lessons in the distance education process; they preferred formal education to distance education; and they found distance education insufficient to meet the individual needs of students in learning. In addition, teachers stated that they found family participation in distance education and teacher–student peer interaction insufficient. The results obtained from the research revealed the necessity of eliminating the obstacles in the education of the disabled in accordance with the quality of inclusive education.
Keywords: Inclusive education; students with disabilities; special education; special education students